PROMOTING AUTONOMOUS LEARNING THROUGH ONLINE DISCUSSION - Ezra Christina Pondalos; Novi Ernia Saputri; Theodesia Lady Pratiwi (Journal of English for Academic and Specific Purposes (JEASP), 2022)
An autonomous learning system is being applied to students nowadays. Students are now encouraged and expected to play a more active role in learning. Autonomy learning is intensified to encourage students to be more independent, creative, and responsible for their learning. Through this article, writers explain how to promote autonomous learning. The method used is the library study related to autonomous learning. Writers explain further about the class design to promote autonomous learning and the strengths also weaknesses of this learning system. Based on this article's findings, possible ways are proposed to help and improve the implementation of autonomous learning.